A novel in-frame mutation in CLN3 leads to Juvenile neuronal ceroid lipofuscinosis in a large Pakistani family. (2nd September 2019) - Sher, Muhammad; Farooq, Muhammad; Abdullah, Uzma; Ali, Zafar; Faryal, Sanam; Zakaria, Mohammad; Ullah, Farid; Bukhari, Hassan; Møller, Rikke S.; Tommerup, Niels; Baig, Shahid Mahmood
Abstract: Aim: Neuronal ceroid lipofuscinosis (NCLs) are the most common neurodegenerative disorders, with global incidence of 1 in 100, 000 live births. NCLs affect central nervous system, primarily cerebellar and cerebral cortices. Juvenile neuronal ceroid lipofuscinosis (JNCL), also known as Batten disease, is the most common form of NCLs. JNCL is primarily caused by pathogenic mutations in CLN3 gene, which encodes a transporter transmembrane protein of uncertain function. The 1.02 kb deletion is the most common mutation in CLN3 that results in frame shift and a premature termination leading to nonfunctional protein. Here, we invetigated a large consanguineous family consisting of four affected individuals with clincal symptoms suggestive of Juvenile neuronal ceroid lipofuscinosis. Materials and methods: We conducted clinial and radilogical investigation of the family and performed NGS based Gene Panel sequencing comprising of five hundred and forty five candidate genes to characterize it at genetic level. Results: We identified a novel homozygous c.181_183delGAC mutation in the CLN3 gene seggregating witht the disorder in the family. The mutation induces in-frame deletion, deleting one amino acid (p.Asp61del) in CLN3 protein. The deleted amino acid aspartic acid plays an important role as general acid in enzymes active centers as well as in maintaining the ionic character of proteins. Conclusion: Our finding adds to genetic variability of Juvenile neuronal ceroid lipofuscinosis associated with CLN3 gene and a predicted CLN3 protein interacting domain site.